People Are Taller in Countries With Better Environmental Conditions - German, Alina; Mesch, Gustavo; Hochberg, Ze'ev (Frontiers in Endocrinology, 2020)
Background: Height is considered an indicator of health and well-being of an individual and population. Height variation results from a complex interaction of genetic, environmental, socioeconomic and cultural influences. In order to understand the contribution of environmental stress associated with the child’s growth, we correlated indicators of a stressful environment with adult height. Methods: We utilized seven equally weighted indicators of a stressful environment: homicide rates, GDP per capita, income inequality(GINI index), corruption perception index(CPI), unemployment rate, urban air pollution, and life expectancy (LE). Data on male and female height by country from 1992-1996 were obtained from the NCD Risk Factor Collaboration dataset. We assessed separately data from the 31 member countries of the Organization for Economic Co-operation and Development (OECD). In order to establish whether the indicators reflected a single conceptual dimension, we conducted an exploratory analysis and principal component analysis (PCA) with orthogonal transformation of the original variables. The relationships between male and female heights and the z-transformed principal components: Quality of life (QoL) and the Social factor (SF) that were derived after the PCA was assessed. Results: Male and female heights strongly correlated (p<0.0001) with each of the seven indicators. In the PCA, the indicators clustered into ‘Quality of Life’ factors (QoL), which comprised the CPI, GDP, air pollution, LE, and 'Social factors' (SF), which comprised homicide rate and GINI index. For males and females, the average height by country strongly correlated with QoL (p<0.0001) and SF (p<0.0001). Within OECD countries, male and female height strongly and negatively correlated with the SF, but not with QoL. Conclusion: Growth attenuation is a tradeoff adaptive response: a calorie used for growth cannot be used for fighting stress. Here we show that: 1.Adult height, when used as a measure of child’s growth, is an indicator of a stressful environment in context with the genetic background and spatial factors; 2.Stressful QoL factors and the SF exert a greater effect on men's height than women's height; and, 3.The ranking of the indicators of short stature are income inequality > air pollution > GDP > CPI > homicide rate > LE > unemployment.